El caso Birdman - Hayder, Mo; Sánchez García-Gutiérrez, Javier; Hayder, Mo. (Madrid : Siruela, 2013)
In Greenwich, England, Inspector Jack Caffery investigates the case of a woman with a live bird sewn in her body. The case is the latest in a series of murders of women whose bodies were surgically mutilated.
Online resource; title from ePub title page (Digitalia, viewed April 8, 2016)
Keywords: Caffery, Jack -- (Fictitious character) -- Fiction; Police -- England -- London -- Fiction; Stripteasers -- Crimes against -- Fiction; Prostitutes -- Crimes against -- Fiction; London (England) -- Fiction; Serial murders -- Fiction; Detective and mystery fiction; Psychological fiction; Electronic books